Lipidomic, Transcriptomic, and BSA-660K Single Nucleotide Polymorphisms Profiling Reveal Characteristics of the Cuticular Wax in Wheat - Zheng, Jun; Yang, Chenkang; Zheng, Xingwei; Yan, Suxian; Qu, Fei; Zhao, Jiajia; Pei, Yanxi (Frontiers in Plant Science, 2021)
Plant epidermal wax helps protect plants from adverse environmental conditions, maintains the function of tissues and organs, and ensures normal plant development. However, the constituents of epidermal wax and the regulatory mechanism of their biosynthesis in wheat have not been fully understood. Wheat varieties with different wax content, Jinmai47 and Jinmai84, were selected to comparatively analyze their waxy components and genetic characteristics, using a combination of lipidomic, transcriptomic, and BSA-Wheat 660K chip analysis. Through lipidomic analysis, 1287 lipid molecules were identified representing 31 lipid subclasses. Among these, Diacylglycerols (DG), (O-acyl)-ω-hydroxy fatty acids (OAHFA), wax ester (WE), Triacylglycerols (TG), and Monoradylglycerols (MG) accounted for 96.4% of the total lipids in Jinmai84 and 94.5% in Jinmai47. DG, OAHFA, and WE were higher in Jinmai84 than in Jinmai47 with the content of OAHFA 2.88-fold greater and DG 1.66-fold greater. Transcriptome sequence and bioinformatics analysis revealed 63 differentially expressed genes related to wax biosynthesis. Differentially expressed genes (DEGs) were found to be involved with the OAHFA, DG, and MG of synthesis pathways, which enriched the wax metabolism pathway. Non-glaucous and glaucous bulks from a mapping population were used to identify single nucleotide polymorphisms (SNP) via 660K chip analysis. Two loci centered on chromosomes 2D and 4B were detected and the locus on 4B is likely novel. These data improve understanding of complex lipid metabolism for cuticular wax biosynthesis in wheat and lay the foundation for future detailed investigation of mechanisms regulating wax metabolism.